Influences of S100A8 and S100A9 on Proliferation of Nasopharyngeal Carcinoma Cells through PI3K/Akt Signaling Pathway. (24th September 2021) - Wen, Liting; Ding, Yu; Chen, Xiaodong; Tian, Keyong; Li, Danfeng; Liang, Kun; Yue, Bo
Abstract : Objective . To investigate the effects of S100A8 and S100A9 on proliferation in nasopharyngeal carcinoma cells and the regulatory effects of PI3K/Akt signaling pathway. Methods . Nasopharyngeal carcinoma cells (CNE1) were cultured and randomly divided into three groups: control group, S100A8/S100A9 overexpression group, and siRNA S100A8/S100A9 group. CCK-8 method was used to detect the effect of S100A8 and S100A9 on the viability of nasopharyngeal carcinoma cells. The effects of S100A8 and S100A9 on the colony forming ability of nasopharyngeal carcinoma cells were detected by colony forming assay. The effects of S100A8 and S100A9 on the proliferation of nasopharyngeal carcinoma cells were detected by EdU staining. The mRNA levels of PI3K and Akt were detected by RT-PCR. The expression levels of PI3K and Akt in NPC cells were detected by Western blot. Wortmannin, an inhibitor of PI3K/Akt pathway, was used to inhibit the activation of PI3K/Akt pathway. Results . Compared with the control group, the cell viability, the number of plate clones, the positive rate of EdU staining, and the mRNA and protein levels of PI3K and Akt were increased in the overexpression group. Compared with the control group, the cell viability, the number of plate clones, the positive rate of EdU staining, and the mRNA and protein levels of PI3K and Akt were decreased in the siRNA group. After inhibiting the activation of PI3K/Akt pathway, the viability of NPC cells in the overexpression group decreased significantly at 48 h and 72 h, while that in the siRNA group increased significantly. Conclusion . SiRNA S100A8 and S100A9 could inhibit the proliferation of nasopharyngeal carcinoma cells, and the underlying mechanism may be related to the inhibition of PI3K/Akt signaling pathway.